(untitled) - Maxwell, Robert L. (Chicago, IL, 1997)
Included the 1993 Amendments of the joint steering committee for revision of Anglo-American cataloguing rulers; provided all examples in the widely used MARC format; considered rule interpretations of the major Anglo-American national libraries; updated all of the chapters; added a completely new chapter on manuscripts to correspond with AACR2R.
Keywords: Descriptive cataloging; Rules